Meanings and interchangeability of continuing professional development, training and education and their connection and influence on learning and development in built environment - Zuhairuse Md Darus,; Fadzil Hassan,; Masran Saruwono,; Zaidi Omar,; Zulkilee Samad,; Fadhil Muhamad,; Noraziah Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2009)
Problems associated with the performance, delivery and quality of products or services due to the ineffective performance of workers in the Malaysian construction industry are continually debated. Critics have frequently associated these shortcomings with inadequacies in the education, training, and continuing professional development (CPD), offered to those in the workforce. This paper investigates the underlying concepts for education, training, and CPD, and identifies their differences and similarities. Understanding the similarities and differences among these factors is critically important because these factors signiÞcantly inßuence the design and delivery of effective education, training, and CPD programs. Most importantly, the parties responsible for developing and implementing such programs must understand that all three types of programs must be based on the underlying principle of learning if they are to be effective